India Marine Fisheries : Issues, Opportunities and Transitions for Sustainable Development - World Bank (World Bank, 2012)
This study represents a collaborative initiative by the World Bank and the Department of Animal Husbandry, Dairying and Fisheries Ministry of Agriculture, Government of India, to review the marine fisheries sub-sector, within a broader sector that also includes aquaculture and inland fisheries. The policy note provides a major step forward in understanding current issues and future opportunities facing the marine fisheries sub-sector. The marine fishing sub-sector accounts for approximately one percent of national Gross Domestic Product (GDP), but forms an important component of the rural coastal economy, generating income, employment, livelihoods, and food security for an estimated 3.52 million people along the 8,118 km Indian coastline, who depend on fishing for their livelihoods. The study represents an initial analytical review of the Indian marine sub-sector with special emphasis on inshore waters, which faces the greatest challenges for management and sustainable development. The main objectives of the study were to: a) appraise the general structure, conduct and performance of the marine fisheries sub-sector in India with particular focus on the role that marine fishery plays in rural livelihoods for coastal communities; b) identify the main constraints in the marine sub-sector that are impacting on biological sustainability and economically healthy fisheries; c) draw on national and international experience to recommend alternative policy approaches and strategies to address these issues; and d) inform the Government of India during subsequent consultations with key stakeholders about long-term transformations towards better sub-sector performance.